Numerical solution and statistical analysis of the unsteady hybrid ferrofluid flow with heat generation subject to a rotating disk - Khashi'ie, Najiyah Safwa; Waini, Iskandar; Hamzah, Khairum; Mukhtar, Mohd Fariduddin; Mohd Kasim, Abdul Rahman; Md Arifin, Norihan; Pop, Ioan (Wiley, 2023)
The goal of this study is to examine the significant parameter of unsteady Fe 3 O 4 ‐CoFe 2 O 4 /H 2 O with heat generation flowing on a rotating disk using numerical and statistical approaches. The mathematical model respected to time‐dependent is first transformed into a set of ordinary differential equations (ODEs) by using similarity variables. The computation is done by employing bvp4c method utilizing MATLAB software. The validation of present model and the output is done by direct comparison with the established report in literature and found to be in a very good agreement. It is worth to mention the presence computation produces up to third solutions. The variations of skin friction coefficient for radial and azimuthal directions including Nusselt number for different value of magnetic parameter, suction parameter, and heat generation parameter are plotted graphically. A Response Surface Methodology (RSM) is applied to scrutinize the physical parameters that affect the response functions under a given set of assumptions. It is revealed the values of skin friction coefficients significantly affected by the magnetic and suction parameters whereas the values of thermal rate are influenced by magnetic, suction, and heat generation parameters.